Expression of HMGCS2 in intestinal epithelial cells is downregulated in inflammatory bowel disease associated with endoplasmic reticulum stress - Martín-Adrados, Beatriz; Wculek, Stefanie K.; Fernández-Bravo, Sergio; Torres-Ruiz, Raúl; Valle-Noguera, Ana; Gomez-Sánchez, Maria José; Hernández-Walias, José Carlos; Ferreira, Frederico Moraes; Corraliza, Ana María; Sancho, David; Esteban, Vanesa; Rodriguez-Perales, Sandra; et al. (Frontiers in Immunology, 2023)
Introduction The Unfolded Protein Response, a mechanism triggered by the cell in response to Endoplasmic reticulum stress, is linked to inflammatory responses. Our aim was to identify novel Unfolded Protein Response-mechanisms that might be involved in triggering or perpetuating the inflammatory response carried out by the Intestinal Epithelial Cells in the context of Inflammatory Bowel Disease. Methods We analyzed the transcriptional profile of human Intestinal Epithelial Cell lines treated with an Endoplasmic Reticulum stress inducer (thapsigargin) and/or proinflammatory stimuli. Several genes were further analyzed in colonic biopsies from Ulcerative Colitis patients and healthy controls. Lastly, we generated Caco-2 cells lacking HMGCS2 by CRISPR Cas-9 and analyzed the functional implications of its absence in Intestinal Epithelial Cells. Results Exposure to a TLR ligand after thapsigargin treatment resulted in a powerful synergistic modulation of gene expression, which led us to identify new genes and pathways that could be involved in inflammatory responses linked to the Unfolded Protein Response. Key differentially expressed genes in the array also exhibited transcriptional alterations in colonic biopsies from active Ulcerative Colitis patients, including NKG2D ligands and the enzyme HMGCS2. Moreover, functional studies showed altered metabolic responses and epithelial barrier integrity in HMGCS2 deficient cell lines. Conclusion We have identified new genes and pathways that are regulated by the Unfolded Protein Response in the context of Inflammatory Bowel Disease including HMGCS2, a gene involved in the metabolism of Short Chain Fatty Acids that may have an important role in intestinal inflammation linked to Endoplasmic Reticulum stress and the resolution of the epithelial damage.